1981
DOI: 10.3109/10826088109038917
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Alcoholism in a Multiracial Society

Abstract: Demographic characteristics of all patients with a diagnosis of alcoholism or alcoholic psychoses admitted between 1975 and 1978 to the Psychiatry Department, General Hospital, Kuala Lumpur, were examined. The diagnosis of alcoholism or alcoholic psychoses accounted for 2% of the total psychiatric admissions. Males greatly predominated over females and Indians greatly predominated over Malays and Chinese. Reasons for these differences are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…He found that alcohol abuse was not a differentiating characteristic of families with a history of suicide, with alcohol abuse identified in 79% of families of suicides and 67% of families of controls, not a statistically significant difference. This study replicated previous studies by Buhrich, Haq, and George (1981) and Saroja, Kasmini, and Kyow (1993), which found a high percentage of alcoholism in the Indian community in Malaysia. Maniam (1995), analysing official government statistics for suicide from 1966 to 1990, found that, while the official Malaysian suicide rate had decreased from a mean of 6.1 per 100,000 in 1966-1974 to a mean of 1.6 per 100,000 in 1975-1990, there had been a corresponding increase in the rate of 'deaths due to undetermined violence' .…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…He found that alcohol abuse was not a differentiating characteristic of families with a history of suicide, with alcohol abuse identified in 79% of families of suicides and 67% of families of controls, not a statistically significant difference. This study replicated previous studies by Buhrich, Haq, and George (1981) and Saroja, Kasmini, and Kyow (1993), which found a high percentage of alcoholism in the Indian community in Malaysia. Maniam (1995), analysing official government statistics for suicide from 1966 to 1990, found that, while the official Malaysian suicide rate had decreased from a mean of 6.1 per 100,000 in 1966-1974 to a mean of 1.6 per 100,000 in 1975-1990, there had been a corresponding increase in the rate of 'deaths due to undetermined violence' .…”
Section: Introductionsupporting
confidence: 92%
“…A potentially important factor missing in these studies was alcohol abuse. Although a number of studies (Buhrich et al, 1981;Maniam, 1994aManiam, , 1994b Transcultural Psychiatry 38(1) Saroja et al, 1993) has found alcohol abuse to be a significant problem in the Indian community, in Malaysia, it was not reported as significantly related to suicides or suicide attempts in any of the studies reviewed, a finding in marked contrast to Western countries (Weissman, 1974).…”
Section: Alcohol Abusementioning
confidence: 97%